Evaluation of the Effect of Protective Sleeve on Output Intensity of Light Emitting Diode Light Cure Units - Amit Jena; Satyajit Mohapatra; Govind Shashirekha (Mashhad University of Medical Sciences, 2016)
Aim: The purpose of this study was to compare the difference in the output intensity of Light Emitting Diode (LED) light cure (LC) devices with and without a protective sleeve and its clinical significance.  Materials and Methods: The output intensity of 152 LC units in dental offices across the state of Odisha were examined. The collection of related information included an average number of exposures per day and the charging status. LED Radiometer (SDI Ltd, VIC, AUS) was used for measuring output intensity.  Results: Out of all the 152 LC devices examined, 137 were found to emit light intensity above minimum baseline values when used with a protective sleeve. The decrease in output intensity, when used with a protective sleeve was statistically significant (p